Perspektif Maqashidus Syari’ah Menyikapi Dinamika Hukum Ketatanegaraan Islam - Yasid; Makhshushi Zakiyah (Fakultas Hukum Universitas Islam Indonesia, 2022)
The concept of a nation state with a very diverse population triggers the need for new analytical tools in religious studies. This is solely to find the legal standing element in the area of contemporary religious studies. In the context of the Unitary State of the Republic of Indonesia (NKRI), the existence of Pancasila as the ideology needs to acquire its legal standing by using a certain theoretical perspective. In Islamic jurisprudence (ushul fiqh) there is knowledge of maqashid sharia which can serve as an analytical tool in conducting studies of Islamic constitutional law, including the ideology of Pancasila. This study examines 3 (three) issues: first, what is the role of maqashid sharia in religious research such as Islamic constitutional law? Second, what is the role of maqashid sharia in responding to the dynamics of Islamic constitutional law? Third, what is the perspective of maqashid sharia on the principles of Pancasila as the ground and ideology of the NKRI? By using normative juridical research method, this study concludes: first, religious research, including Islamic state administration, requires adequate theoretical tools (maqashid sharia) for it can produce findings that are in accordance with the development of the society; second, the dynamics of Islamic constitutional law is shown by the shift in the form of government from the caliphate system, to the kingdom to democracy, so that religious arguments do not direct certain forms of state and government; third, the principle of Pancasila as the basis and ideology of the NKRI has been proven to be able to unite the nation and create harmony in the midst of the diversity and plurality of the people. Key Words: Maqashidus syari’ah; Pancasila; Islamic law; Islamic constitution; benefit Abstrak Konsep negara bangsa dengan penduduk yang sangat majemuk memicu kebutuhan perangkat dan alat analisis baru dalam kajian keagamaan. Hal tersebut demi menemukan aspek legal standing dalam wilayah kajian keagamaan kontemporer. Dalam konteks Negara Kesatuan Republik Indonesia (NKRI), keberadaan ideologi Pancasila perlu mendapatkan legal standing tersebut dengan menggunakan perspektif teori tertentu. Dalam yurisprudensi Islam (ushul fiqh) terdapat ilmu maqashidus syari’ah yang bisa berperan menjadi alat analisis dalam melakukan kajian hukum ketatanegaraan Islam, termasuk tentang ideologi Pancasila. Penelitian ini mengkaji mengenai 3 (tiga) hal: pertama, bagaimana peran maqashidus syari’ah dalam penelitian keagamaan seperti hukum ketatanegaraan Islam? Kedua, bagaimana peran maqashidus syari’ah menyikapi dinamika hukum ketatanegaraan Islam? Ketiga, bagaimana perspektif maqashidus syari’ah tentang asas Pancasila sebagai dasar dan ideologi NKRI? Dengan menggunakan metode penelitian yuridis normatif, penelitian ini berkesimpulan: pertama, penelitian keagamaan, termasuk ketatanegaraan Islam, memerlukan perangkat teori yang memadai (maqashidus syari’ah) sehingga dapat menghasilkan temuan yang sesuai dengan perkembangan masyarakat; kedua, dinamika hukum ketatanegaraan Islam ditunjukkan dengan adanya pergeseran bentuk pemerintahan dari sistem kekhilafahan, kerajaan kemudian demokrasi, sehingga argumen keagamaan tidak mengarahkan bentuk negara dan pemerintahan tertentu; ketiga, asas Pancasila sebagai dasar dan ideologi NKRI terbukti dapat menyatukan bangsa serta menciptakan kerukunan di tengah keragaman dan kemajemakan penduduk. Kata Kunci: Maqashidus syari’ah; Pancasila; fikih; ketatanegaraan Islam; kemaslahatan